Ethephon-Mediated Bloom Delay in Peach Is Associated With Alterations in Reactive Oxygen Species, Antioxidants, and Carbohydrate Metabolism During Dormancy - Islam, Md Tabibul; Liu, Jianyang; Sherif, Sherif M. (Frontiers in Plant Science, 2021)
Ethephon (ET) is an ethylene-based plant growth regulator (PGR) that has demonstrated greater efficacy in delaying bloom in deciduous fruit species. However, the underlying mechanisms by which ET modulates dormancy and flowering time remain obscure. This study aimed to delineate the ET-mediated modulations of reactive oxygen species (ROS), antioxidants, and carbohydrate metabolism in relation to chilling and heat requirements of ‘Readhaven’ peach trees during dormancy. Peach trees were treated with ethephon (500 ppm) in the fall (at 50% leaf fall), and floral buds were collected at regular intervals of chilling hours (CH) and growing degree hours (GDH). In the control trees, hydrogen peroxide (H2O2) levels peaked at the endodormancy release and declined thereafter; a pattern that has been ascertained in other deciduous fruit trees. However, H2O2 levels were higher and sustained for a more extended period than control in the ET-treated trees. ET also increased the activity of ROS generating (e.g. NADPH-oxidase; superoxide dismutase) and scavenging (e.g., catalase, CAT; glutathione peroxidase) enzymes during endodormancy. However, CAT activity dropped significantly just before the bud burst in the ET-treated trees. In addition, ET affected the accumulation profiles of starch and soluble sugars (hexose and sucrose); significantly reducing the sucrose and glucose levels and increasing starch levels during endodormancy. However, our study concluded that variations in ROS levels and antioxidation pathways, rather than carbohydrate metabolism, could explain the differences in bloom time between ET-treated and -untreated trees. The present study also revealed several important bud-dormancy controlling factors that are subject to modulation by ethephon. These factors can serve as potential targets for developing PGRs to manipulate bloom dates in stone fruits to avoid the ever-increasing threat of spring frosts.